Organização do trabalho colaborativo para inclusão - Gomes, Valéria Carla Vieira (2022)
Thinking about an Inclusive Education is looking for tools and strategies to provide work that aims at the participation and learning of all students. The organization of collaborative work among professionals is one of the aspects that can help in this process, especially in the inclusion of students target audience of special education (PAEE). In this sense, the research was conducted in a public school located in the North Zone of Natal/RN and had the general objective: to develop, implement and evaluate continuing education, with a view to organizing collaborative work for the inclusion of all students, together with to Elementary School teachers, management, coordination, Special Education teachers, Libras interpreter teachers and SRM teachers. And, as specific objectives: 1) accompany the expansive learning during training; 2) reflect on the organization of collaborative work for school inclusion; 3) understand the potential of collaborative training for the organization of work at school and 4) produce a guide for collaborative teachers training in school contexts. The research was guided by the CulturalHistorical Activity Theory, highlighting the understanding of expansive learning, theorized by Engeström (2002, 2016), which concerns the collective production of new learning, of changes. It is configured as a collaborative research (IBIAPINA, ALBUQUERQUE, 2016), which had data produced from interviews, questionnaires and, mainly, training with teachers. This training is understood as a formative intervention that is characterized as the organization of a transformation process, constantly remodeled by the organizational dynamics and internal politics and by the specific conditions that it encounters or creates (ENGESTRÖM, 2011). The formative intervention had ten online meetings, supported by the Google Meet platform, held between October 2021 and June 2022, with the aim of creating spaces for sharing and building learning for the organization of inclusive collaborative work. The data were interpreted from the discursive textual analysis (MORAES, 2003), having as axis the actions of expansive learning. Thus, the training discussions focused on questioning actions, historical and empirical analysis, modeling and examination of the new model; it was not possible to complete the expansive learning cycle with consolidation of the new practices discussed. One sought reflection and construction of tools that would contribute to collaborative work and inclusion in the school; the questioning actions turned to the organization of planning and to the articulations between professionals; analysis actions sought to understand the context and organization of collaborative work in the institution; modeling actions took shape in the creation of an organization chart and the use of the institution's Drive as tools for resolving the questions posed; examining the new model focused on pointing out difficulties in using the Drive. Linked to the expansive learning category, inclusion, collaboration, planning, teacher training were also discussed, categories that were intertwined throughout the textual construction. The research reflections were also the basis for the construction of a collaborative training guide, a product that is a requirement of the professional master's degree. One can see the potential of collaborative work for building inclusive practices, considering both the daily work at school and the work carried out in training.